Legal Studies In Secondary Schools: the New South Wales Experience - Patty Kamvounias (Legal Education Review)
The extraordinary growth and popularity of legal studies in New South Wales secondary schools clearly demonstrates the interest of school students in the law and confirms that legal education is not the exclusive domain of the universities. Much of the literature on legal education focuses on tertiary legal education with very little attention being given to legal education in secondary schools.1 What exactly is being taught in the secondary school legal studies courses? How and by whom should such courses be taught? In this article, I outline the content of the legal studies courses in New South Wales and argue that the current courses and the plans for further developments are overly ambitious for several reasons, including, that the course content has not been kept to reasonable limits and that in some instances may be overly technical. As part of my argument, I discuss the assistance currently offered to legal studies teachers to illustrate the ambitious nature of the courses in New South Wales. Secondary school teachers are not lawyers, yet they are being called upon to teach “law” or more correctly, to teach “about the law”. Being “teachers” they know how to teach but now they are necessarily concentrating on what to teach.